Employment Stereotypes From Three Largest Muslim in Southeast Asia - Ririn Nopiah; Eka Dewi Anggraini; Musdir (UIN Sulthan Thaha Saifuddin Jambi, 2023)
Employment is one of the main instruments of a country in providing social welfare. Society's perception of job often get comparisons between rights and gender. Various factors that cause society to judge employment have certain limitations and assessments. This study to analyzes the comparison of public stereotypes of employment in the three largest Muslim countries in Southeast Asia. This study uses world value survey data batch 7 (2017-2022) with ordered logit analysis. The results shows that Public perception of the primacy of men's rights in getting a job, public perception of the preference of local residents over foreigners in job giving, and public perception of the negative effects of women's emancipation at working are still relative high influenced by individual religiousity level, the role of social capital, democratic level in that country, and variable of demographic.